Nutritional Composition and Biological Characteristic of Talbina Drink - Oraif, Sahar Sami M. (2011)
Talbina is a beverage made by cooking 2 table spoons of barley wholegrain flour and a cup of water for 30 minutes then adding a cup of milk and 1 tablespoon of bee’s honey as a sweetener. Even the Talbina had been recommended by the Prophet Mohamed (peace be upon him) to be drunk for the sick and grieving people, it has not have been studied nor defined by the scientific community. Therefore, this study was aimed to initially define the Talbina by measuring its nutritional composition values with its components (whole grain barley flour, honey and milk) in terms of their proximate composition analyses followed by investigating the biological characteristic of Talbina and its components by determining their antioxidant vitamins content, antioxidant and toxicity effects of Talbina against human colon cancer cell line. Using the AOAC methods, the proximate nutritional composition values of Talbina and its components were analyzed such as total carbohydrate, crude fat, total dietary fiber, crude protein, total ash and antioxidant vitamins. Talbina contained the basic nutritional components. Moisture content exceed 85%, total carbohydrate content was 8.17 ±0.31g/ 100g of sample, crude fat was 3.91 ±0.06g , total dietary fiber was 1.83 ±0.1 g, crude protein reached 1.82 ±0.01g and total ash was 0.5 ±0.01g. However, Talbina was not rich in antioxidant vitamins (vitamin A, C and E) which might be correlated with the possible antioxidant activity. Results showed significant differences in the content of certain macronutrients compared with its components. HPLC analysis showed Talbina has no vitamin A, low content of vitamins C (ascorbic acid equivalent = 7.60 ±0.26 mg/100g) and E (α tocopherol equivalent = 66 ±2.58 μg/ 100g). According to the β-carotene bleaching method and DPPH free radical scavenging method, antioxidant activity of Talbina was negligible, only the total phenolic content of the Talbina has gave a significant difference comparing with barley in a value of 38.58 ±3.86 mg gallic acid equivalent /100g of sample using Folin- Ciocalteu method. In MTT assay, Talbina methanolic extract showed toxicity activity against HT-29 colon cancer cell line, since IC50 exceeded 76 μg/ ml after 96 hours of exposing incubation. Generally, Talbina produce a whole nutritionally serving beverage with all basic macronutrients but boiling Talbina could reduce significantly the antioxidant vitamins and activity.